2004
DOI: 10.1182/blood-2004-04-1506
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of engraftment in patients with hematologic malignancies given allogeneic hematopoietic cell transplantation after nonmyeloablative conditioning

Abstract: We analyzed the kinetics of donor engraftment among various peripheral blood cell subpopulations and their relationship to outcomes among 120 patients with hematologic malignancies given hematopoietic cell transplantation (HCT) after nonmyeloablative conditioning consisting of 2 Gy total body irradiation (TBI) with or without added fludarabine. While patients rapidly developed high degrees of donor engraftment, most remained mixed donor/ host chimeras for up to 180 days after HCT. Patients given preceding chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(216 citation statements)
references
References 35 publications
11
201
2
2
Order By: Relevance
“…A more rapid induction of T-cell chimerism has been observed in other studies of RIST in patients who had been previously treated with chemotherapy for diseases other than CML or MDS [24]. Although a close association between the occurrence of acute GvHD and the induction of higher levels of donor T-cell chimerism has been reported [14], in our experience over 50% of patients did not achieve complete chimerism at the onset of acute GvHD, demonstrating that mixed chimerism status did not provide absolute protection from GvHD, which is in agreement with data published by Baron et al [15]. We speculate that differences in the conditioning regimen and GvHD prophylaxis may result in different observations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A more rapid induction of T-cell chimerism has been observed in other studies of RIST in patients who had been previously treated with chemotherapy for diseases other than CML or MDS [24]. Although a close association between the occurrence of acute GvHD and the induction of higher levels of donor T-cell chimerism has been reported [14], in our experience over 50% of patients did not achieve complete chimerism at the onset of acute GvHD, demonstrating that mixed chimerism status did not provide absolute protection from GvHD, which is in agreement with data published by Baron et al [15]. We speculate that differences in the conditioning regimen and GvHD prophylaxis may result in different observations.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, there has been no study to prospectively assess whether RIST consisting of 180 mg fludarabine plus 8 mg/kg busulfan without antithymocyte globulin actually produces less significant organ toxicities and treatment-related toxicities in an older patient population. Information regarding the impact of the speed and degree of lineage-specific donor chimerism on clinical outcomes after RIST in older patients has been limited [3,8,[13][14][15][16][17]. Moreover, even studies evaluated with more homogeneous patient population, type of GvHD prophylaxis and/or tempo of withdrawal of immunosuppressive agents varied depending on transplant centers and a feasible prophylaxis regimen for acute GvHD has not been well evaluated in RIST, which is considered to require a sophisticated balance between GvHD and a graft-versus-leukemia (GvL) effect.…”
Section: Introductionmentioning
confidence: 99%
“…Other regimens associate cyclophosphamide and fludarabine, or anti-thymocyte globulin (ATG) and total lymphoid irradiation (TLI) (8 Gy) with postgrafting immunosuppression also consisting in MMF and CSP [12]. These types of conditioning regimens produce only mild myelosuppression and little regimen-related toxicity, making them realizable in an outpatient setting [13]. Following nonmyeloablative conditioning, antitumor responses may require extended periods of time.…”
Section: Nonmyeloablative Versus Reduced Intensity Conditioning Regimensmentioning
confidence: 99%
“…McSweeney et al reported a 20% graft rejection rate 2-4 months after HSCT with TBI alone as nonmyeloablative conditioning regimen [17]. High levels (>50%) of donor T-and NK-cell chimerism one month after transplantation are associated with a lower risk of graft rejection [13].…”
Section: Engraftment: Mixed Chimerism and Risk Of Graft Rejectionmentioning
confidence: 99%
See 1 more Smart Citation